Downregulation of microRNA‐15b by hepatitis B virus X enhances hepatocellular carcinoma proliferation via fucosyltransferase 2‐induced Globo H expression. Issue 7 (15th October 2013) - Wu, Chen‐Shiou; Yen, Chia‐Jui; Chou, Ruey‐Hwang; Chen, Jia‐Ni; Huang, Wei‐Chien; Wu, Chung‐Yi; Yu, Yung‐Luen
<x xml:space="preserve">Abstract</x> Globo H, a cancer‐associated carbohydrate antigen, is highly expressed in various types of cancers. However, the role of Globo H in hepatocellular carcinoma (HCC) remains elusive. In our study, we performed glycan microarray analysis of 134 human serum samples to explore anti‐Globo H antibody changes and found that Globo H is upregulated in hepatitis B virus (HBV)‐positive HCC. Similarly, immunohistochemistry showed that Globo H expression was higher in tumors compared to normal tissues. In addition, fucosyltransferase 2 (FUT2), the main synthetic enzyme of Globo H, was also increased in HCC cells overexpressing HBV X protein (HBX). HBX plays an important role in promoting cell proliferation and may be related to increased levels of FUT2 and Globo H. Furthermore, using microRNA profiling, we observed that microRNA‐15b (miR‐15b) was downregulated in patients with HCC and confirmed association of FUT2 expression with expression of its product, Globo H. Therefore, our results suggest that HBX suppressed the expression of miR‐15b, which directly targeted FUT2 and then increased levels of Globo H to enhance HCC cell proliferation. Additionally, proliferation of HBX‐overexpressing HCC cells was significantly inhibited by treatment with Globo H antibody in vitro. In xenograft animal experiments, we found that overexpression of miR‐15b effectively suppressed tumor growth. The newly identified HBX/miR‐15b/FUT2/Globo H axis suggests one possible molecular mechanism of HCC cell proliferation and represents a new potential therapeutic target for HCC treatment.